Antibacterial performance enhancement using hydrophobic deep eutectic solvents: COSMO-RS prediction, experimental validation, and synergistic action with antibiotics - Elgharbawy, Amal A.M.; Khan, Huma Warsi; Mohd Noor, Najihah; Syed Putra, Sharifah Shahira; Engku Ismail, Engku Normi; Hizaddin, Hanee Farzana; Hayyan, Maan; Hayyan, Adeeb; Basirun, Wan Jefrey; Moniruzzaman, Muhammad; Al-afandi, Lama; Abdullah Sani, Muhamad Shirwan (Elsevier, 2024)
Microbial infection is a hazardous and challenging clinical problem that has attracted considerable attention recently, primarily owing to the noticeable rise in antimicrobial resistance. To address the medical requirements to encounter this dilemma, we present hydrophobic deep eutectic solvents (HDESs) that combine experimental research and computational prediction; conductor-like screening model for real solvents (COSMO-RS). Mentholbased HDESs were successfully obtained when mixed with fatty acids, and their thermal profiles were analyzed. The HDES systems and their synergistic effects demonstrated potent antimicrobial activity against Gram-positive and Gram-negative bacteria, with DES 4 (menthol:decanoic acid) exhibiting the highest bactericidal activity at a molar ratio of 1:5. The interaction between the HDESs and bacterial cell wall structural compounds was confirmed by field-emission scanning electron microscopy and Fourier transform infrared spectroscopy. The results revealed a favorable concurrence between the projected and empirical outcomes, indicating that DES 4 exhibited bacteriostatic properties and could be a viable substitute for managing bacterial infections of diverse origins. In addition, the synergistic effect of DES 4 and tetracycline showed promising potential. The successful integration of experimental and computational approaches in this study also sets a precedent for the rational design of future antimicrobial agents and opens new avenues for tackling other clinical challenges.